2021
DOI: 10.1002/hpm.3387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for hierarchical diagnosis and treatment policy proposals in China: A novel multi‐attribute group decision‐making method with multi‐parametric distance measures

Abstract: The policy 'hierarchical medical treatment system' promulgated by the State Council of China is an effective way to solve the problem of insufficient and unbalanced medical resources. In response, governments in different provinces ex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The regional allocation of resources is poorly balanced, with a large number of high-quality medical resources concentrated in large cities and central areas [ 22 , 23 , 24 ]. In recent years, some scholars have focused on the tiered differences in resource allocation, arguing that the polarization of medical resources between primary care facilities and hospitals is prominent and that medical resources are allocated in an inverted triangle among multi-tier healthcare institutions [ 5 , 25 , 26 ]. However, most of them are based on a national scale and lack an in-depth analysis of tiered differences at the small regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…The regional allocation of resources is poorly balanced, with a large number of high-quality medical resources concentrated in large cities and central areas [ 22 , 23 , 24 ]. In recent years, some scholars have focused on the tiered differences in resource allocation, arguing that the polarization of medical resources between primary care facilities and hospitals is prominent and that medical resources are allocated in an inverted triangle among multi-tier healthcare institutions [ 5 , 25 , 26 ]. However, most of them are based on a national scale and lack an in-depth analysis of tiered differences at the small regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…The positive relationships between health resources and sense of city belonging among MEFFs with hypertension and diabetes indicated that public policymakers should improve medical supply, including number of doctors and hospitals, and access to health education. Hierarchical diagnosis and treatment policy (HDTP) is the key to improving both efficiency and quality of the medical service system, and solving the problem of insufficient and unbalanced medical resources [ 70 , 71 ]. Elderly migrants suffer from more chronic diseases may face the problem of the difficulty in seeing a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-attribute decision-making based on soft sets refers to the decision-making problem of selecting the optimal alternative or ranking the alternatives when considering multiple attributes. At present, it is widely used in medical diagnosis [1,2] , environmental risk identification [3] , teaching quality assessment [4] , supplier selection [5] and other fields [6,7] . It can be seen that the main problems solved by multi-attribute decision-making are evaluation and selection [8,9] .…”
Section: Introductionmentioning
confidence: 99%